2018
DOI: 10.2147/rru.s178902
|View full text |Cite
|
Sign up to set email alerts
|

The role of ultrasonography in detecting urinary tract calculi compared to CT scan

Abstract: ObjectiveTo evaluate the accuracy of ultrasonography (US) in measuring the urinary tract stone using non-contrast computed tomography (NCCT) as the standard reference.Patients and methodsA total of 184 patients suspected with urolithiasis who had undergone NCCT and US radiologic investigation from 2015 to 2017 were enrolled in this study. The sensitivity, specificity, and stone size measured in US were validated by NCCT. Data of the stone size in US were classified into four groups (0–3.5, 3.6–5, 5.1–10, >10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 12 publications
(19 reference statements)
1
24
0
Order By: Relevance
“…This result is consistent with Ahmed et al . who reported that urinary stone size is usually the same for both US and CT.[ 8 ] The results are also consistent with Sade et al ., who reported that the diagnostic accuracy of US and low dose CT for the diagnosis of urolithiasis in pediatric patients, were 0.68 and 1, respectively. [ 18 ] However, this result was not consistent with the results of Dai et al ., who reported that the mean stone size was 6.8 ± 4 mm for CT and 10.3 ± 4.1 mm for US.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result is consistent with Ahmed et al . who reported that urinary stone size is usually the same for both US and CT.[ 8 ] The results are also consistent with Sade et al ., who reported that the diagnostic accuracy of US and low dose CT for the diagnosis of urolithiasis in pediatric patients, were 0.68 and 1, respectively. [ 18 ] However, this result was not consistent with the results of Dai et al ., who reported that the mean stone size was 6.8 ± 4 mm for CT and 10.3 ± 4.1 mm for US.…”
Section: Discussionsupporting
confidence: 91%
“…[ 7 ] The sensitivity of US is low in stones with low-grade hydronephrosis or hydro calyces, and small stones (<3 mm). [ 8 ] The sensitivity of US increases with increasing stone size, but CT is still the gold standard for detecting urinary stones. [ 7 8 ] Measuring the stone size is an important point for planning management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early stone-free rate (SFR) after operation was 90.2% (101 patients) on the first day after operation in accordance with KUB X-ray or US ( 14 ), but 6 patients had residual fragment <5 mm, which passed spontaneously 2 weeks after the operation (total SFR reached 95.3% without any axillary procedure). Three patients underwent second-look nephroscopy, and ureteroscopy was done for two patients due to migrated stone fragments to the distal ureter.…”
Section: Resultsmentioning
confidence: 99%
“…More commonly seen in patients within age group of 35-45. American guideline recommends CT scan as first choice for ureteric stone diagnosis while European says the ultrasound as the initial modality (4) . Normal renal function is critical because it involves the filtration and excretion of metabolic waste products such as urea and ammonium; electrolyte regulation; fluid and acid-base balance; aids in the formation of red blood cells, which is used to maintain blood pressure through the renin-angiotensin-aldosterone system and to regulate water resorption; and maintain the blood pressure via the renin-angiotensin-aldosterone system and maintain the volume in blood vessels (5) .…”
Section: Introductionmentioning
confidence: 99%